Technical-scientific production and knowledge networks about medicinal plants and herbal medicines in the Amazon - Lepsch-Cunha, Nadja; Muraro, Vinicius; Nascimento, Henrique Eduardo Mendonça; Mazoni, Alysson; Nunez, Cecília Verónica; Bonacelli, Maria Beatriz Machado (Frontiers in Research Metrics and Analytics, 2024)
This paper explores the role of Brazilian research institutions in the global and national context of medicinal plants, most of which have ethnopharmacological use, and herbal medicines related to the Amazon. The research highlights Brazil's position in scientific production and the importance of Amazonian in developing phytomedicines. The study aims to provide an overview of national and international technical-scientific production of medicinal plants and herbal medicines related to the Amazon, focusing on scientific impact, scientific collaboration, Technology Readiness Level (TRL) of scientific production and innovation system maturity. The study employs a comprehensive methodological approach, including data collection from Scopus from 2002 to 2022, data cleaning, bibliometric and network analysis, and TRL classification using advanced natural language processing techniques like Latent Dirichlet Allocation and Jaccard distance measure. The findings reveal a predominant contribution from Brazilian institutions and authors, with 1850 publications analyzed. The study identifies key areas such as Pharmacology, Toxicology, Pharmaceuticals, Medicine, and Biochemistry. It also uncovers the various collaborative networks and technological maturity levels, with a significant focus on early-stage development phases. The research concludes that Brazilian institutions, particularly those in the Amazon region, play an important role in the scientific exploration and development of medicinal plants and herbal medicines. However, other countries such as the USA were proportionally more productive in clinical trial research. The study underscores the potential of Brazil's rich biodiversity and traditional knowledge in the pharmaceutical industry, especially concerning neglected diseases. It suggests a need for stronger research systems and international collaboration to leverage these resources for global health benefits.